Determination of Scientific Name of Faranjmoshk: A Traditional Persian Medicinal Plant - Mahbubeh Bozorgi; Masoud Mirmasoumi; Gholamreza Amin (Tehran University of Medical Sciences, 2017)
Faranjmoshk is one of the seeds that are sold in Iranian herbal markets for various medical purposes including anxiety, spleen disorder and inflammatory bowel disease. For the variety of discussions around different botanical characteristics ofFaranjmoshkin different references,there is no exactscientific name for these seeds. Moreover,Faranjmoshk, basil and lemon balm seeds are incorrectly equaled in somearticles. It is important to distinguish between them.The aim of the present study was to determine the exact scientific nameof Faranjmoshk.For these purpose,purchased seeds from different cities were grown under greenhouse condition up to flower formation. According to morphological analysis of grown plant,available seeds in herbal markets were belonging to Clinopodiumgraveolens (M.Bieb.) Kuntze.  Thus, it is different from lemon balm and basil. Since no phytochemical analyses and pharmacological studies have been performed on Clinopodiumgraveolensdespite of various medicinal uses in traditional Persian Medicine, it is suggested to design studies to evaluate its phytochemistry and pharmacology.